Registration of Intellectual Property Rights for Industrial Designs in the Rattan Industry Sector in Cirebon Regency - Natasya, Allnur Rohimah; Mayaharti, Listia; Hikmatyara, Sintya; Hidayat, Dudung; Solichin, Solichin (PT FORMOSA CENDEKIA GLOBAL, 2025)
The rattan industry in Cirebon Regency routinely produces rattan designs every year, but legal protection for these designs is often ignored, especially regarding industrial design registration. The purpose of this study was to examine the legal awareness of industry players in registering their designs with the DJKI. This study uses a normative legal approach based on secondary and primary data to assess the legal awareness of industry players in registering designs with the Directorate General of Intellectual Property Rights. The results of the study show that the majority of industry players have not registered their industrial designs, while registration provides legal protection against imitation and increases product competitiveness through guarantees of design exclusivity for rights holders.